Пышечка: [роман] / Татьяна Тронина - Тронина Татьяна Михайловна (Дочери Евы, 2017)
Экземпляры: аб. ЦБ (2017.19.09) / Инвентарный номер: 3211 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Т 73 / ББК: 84(2Рос=Рус)6